Evaluation of interleukin-6 in gingival crevicular fluid in patients with periodontitis - Mudasir Gani; Rezhat Abbas; Munaza Rashid (Wolters Kluwer Medknow Publications, 2024)
Introduction: Periodontal diseases are disease processes involving the periodontium, a term that describes the supportive apparatus surrounding a tooth. Periodontitis is when the periodontal condition has progressed beyond gingivitis into a chronic, destructive, and irreversible inflammatory disease state. The bacteria can then penetrate deeper into the tissues and surrounding periodontium, triggering a host response in an attempt to defend against the invading bacteria. Many inflammatory cytokines regulate periodontitis pathophysiology through a cross-talk between tissue and immune cells. Interleukin (IL)-6 is a vital cytokine regulating host response to bacterial infection. Aim: The current study aimed to quantify IL-6 levels in gingival crevicular fluid (GCF) and assess the correlation with periodontitis. Materials and Methods: There were 22 study subjects: 11 study subjects (with periodontitis) and 11 control subjects (with healthy periodontium). The commercial human IL-6 ELISA kit (Elabscience) was used to measure the level of IL-6 as ng IL-6/ml of GCF. Results and Discussion: The control group had a mean ± standard deviation level of IL-6 of 0.56 ± 0.29, whereas the study group had 1.58 ± 0.23. The difference was statistically significant (P < 0.05). Conclusion: IL-6 assessment in GCF has an excellent prognostic role in periodontitis.